2021
DOI: 10.1111/pace.14331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of synchronization between left bundle branch and his bundle pacing in atrial fibrillation patients: An intra‐patient‐controlled study

Abstract: Background His bundle pacing (HBP) is a physiological pacing strategy to preserve the electrical synchrony of ventricular conduction and left ventricular (LV) function. Left bundle branch pacing (LBBP) has emerged as an alternative physiological pacing technique. Objective To evaluate cardiac electrical and mechanical synchrony comparing LBBP and HBP in patients with permanent atrial fibrillation (AF). Methods Consecutive patients with symptomatic bradycardia and AF were enrolled from January to June of 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…In total, four studies ( 17 , 18 , 20 , 22 ) reported R wave amplitudes. As shown in Figure 3A , our study found that the sensed R wave amplitude at implantation of LBBP recipients was larger than HBP recipients (MD: 7.23, 95% CI: 5.29–9.16, P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, four studies ( 17 , 18 , 20 , 22 ) reported R wave amplitudes. As shown in Figure 3A , our study found that the sensed R wave amplitude at implantation of LBBP recipients was larger than HBP recipients (MD: 7.23, 95% CI: 5.29–9.16, P < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In total, four studies ( 17 , 20 22 ) reported the paced capture threshold at implantation and follow-up. A statistically significant difference was observed at implantation and follow-up in capture threshold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPSP, a physiological pacing modality that directly stimulates the conduction system of the heart and maintains synchronization of ventricular electrical activation has produced better results compared to BIVP in clinical practice (41,45). Lustgarten et al (11) summarized the clinical outcome data from a 2015 study of 12 patients with a mean baseline LVEF of 26%; at the 6-month follow-up, HBP was shown to improve by 32% and BIVP by 31% (P = 0.043 and P = 0.02, respectively); the baseline NYHA grades for HBP and BIVP improved from 2.9 to 1.9 (P < 0.01 and P < 0.01, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Further details regarding the studies analyzed are shown in Table 1. The 18 included studies (11,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), which were RCTs and observational studies, were scored using the Jadad scoring system and the NOS quality assessment system, as shown in Figures 2A,B.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%